Genomic Surveillance of Streptococcus pyogenes Strains Causing Invasive Disease, United States, 2016–2017 - Li, Yuan; Rivers, Joy; Mathis, Saundra; Li, Zhongya; Velusamy, Srinivasan; Nanduri, Srinivas A.; Van Beneden, Chris A.; Snippes-Vagnone, Paula; Lynfield, Ruth; McGee, Lesley; Chochua, Sopio; Metcalf, Benjamin J.; et al. (Frontiers in Microbiology, 2020)
Background Streptococcus pyogenes is a major cause of severe, invasive infections in humans. The bacterial pathogen harbors a wide array of virulence factors and exhibits high genomic diversity. Rapid changes of circulating strains in a community are common. Understanding the current prevalence and dynamics of S. pyogenes lineages could inform vaccine development and disease control strategies. Methods We used whole-genome sequencing (WGS) to characterize all invasive S. pyogenes isolates obtained through the Center for Disease Control and Prevention’s Active Bacterial Core surveillance (ABCs) in the U.S. in 2016 and 2017. We determined the distribution of strain features, including emm type, antibiotic resistance genes, and selected virulence factors. Changes in strain feature distribution between years 2016 and 2017 were evaluated. Phylogenetic analysis was used to identify expanding lineages within emm type. Results Seventy-one emm types were identified from 3873 isolates characterized. The emm types targeted by a 30-valent M protein-based vaccine accounted for 3230 (89%) isolates. The relative frequency of emm type was similar between the two years. While all isolates were penicillin-susceptible, erythromycin-resistant isolates increased from 273 (16% of 2016 isolates) to 432 (23% of 2017 isolates), mainly driven by increase of the erm-positive emm types 92 and 83. The prevalence of 24 virulence factors, including 11 streptococcal pyrogenic toxins, ranged from 6 to 90%. In each of the emm types 49, 82, and 92, a subgroup of isolates was found to significantly expand between 2016 and 2017 compared to isolates outside the subgroup (p-values < 6.9 × 10-6). Specific genomic sequence changes were associated with the expanded lineages. Conclusions While overall population structure of invasive S. pyogenes in the U.S. remained stable, some lineages, including a few that were antibiotic-resistant, increased between 2016 and 2017. Continued genomic surveillance can help track and characterize bacterial features associated with emerging strains from invasive infections.